2018
DOI: 10.1016/j.expneurol.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization and electrical stimulation enhance in vitro and in vivo sensory axon growth after spinal cord injury

Abstract: Activity dependent plasticity is a key mechanism for the central nervous system (CNS) to adapt to its environment. Whether neuronal activity also influences axonal regeneration in the injured CNS, and whether electrical stimulation (ES) can activate regenerative programs in the injured CNS remains incompletely understood. Using KCl-induced depolarization, in vivo ES followed by ex-vivo neurite growth assays and ES after spinal cord lesions and cell grafting, we aimed to identify parameters important for ES-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 53 publications
(82 reference statements)
2
40
0
1
Order By: Relevance
“…Highly significant increase was observed at dose of 500 mg/kg in rearing numbers and its duration; these results were almost similar to the standard treatment group which suggests improved locomotor action [19]. While increase in distance travelled at 500 mg/kg on 15 th day shows improved motor activity and central nervous system stimulation [20]. These results reflect low anxiety potential and high exploratory behavior of S. cumini.…”
Section: Discussionsupporting
confidence: 61%
“…Highly significant increase was observed at dose of 500 mg/kg in rearing numbers and its duration; these results were almost similar to the standard treatment group which suggests improved locomotor action [19]. While increase in distance travelled at 500 mg/kg on 15 th day shows improved motor activity and central nervous system stimulation [20]. These results reflect low anxiety potential and high exploratory behavior of S. cumini.…”
Section: Discussionsupporting
confidence: 61%
“…In these studies, conditioning by electrical stimulation was found to elicit greater physiological and functional recovery than conditioning by nerve crush. This apparent discrepancy with the effects observed in vitro and in models of subsequent spinal cord injury (Goganau et al, 2018) is likely due to slowing of the regenerating axons upon reaching the disrupted cytoarchitecture, proliferative Schwann cells, and inflammation at the nerve crush site. The efficacy of both pre-and post-injury electrical stimulation in enhancing regeneration of rodent peripheral nerves and accelerating functional outcomes, together with the feasibility of its use in bedside settings makes brief low frequency electrical stimulation a clinically relevant approach to mediate PNS repair.…”
Section: Functional Effects Of Electrical Stimulation On Circuit Recomentioning
confidence: 57%
“…In addition to the transcriptional regulation that occurs with electrical stimulation, 1 h of low-frequency stimulation of intact rat sciatic nerves increases intracellular cAMP levels in DRG neurons similar to nerve injury (Udina et al, 2008). Despite the fact that electrical stimulation and axotomy induce similar increases in cAMP, 1 h of low-frequency electrical stimulation is not sufficient to fully recapitulate the regenerative response of peripheral conditioning of sensory neurons to a central spinal cord injury (Udina et al, 2008;Goganau et al, 2018).…”
Section: Neuronal Activity and Molecular Control Over Axon Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited intrinsic regenerative capacity of adult sensory axons also contributes to the failure of axon regeneration 16,17 . Lesions of DRGs' central axon branches fail to elicit a robust regenerative response 18,19 . Some interventions have been shown to enhance the intrinsic regenerative response of sensory neurons, including a so-called peripheral "conditioning lesion" [20][21][22] , induction of inflammation near the cell body within the ganglia themselves 14,23 , and driving activation of mTOR in DRG neurons 15 .…”
mentioning
confidence: 99%